2016
DOI: 10.1097/md.0000000000005390
|View full text |Cite
|
Sign up to set email alerts
|

Relapsing–remitting lesions in a woman with progressive hemifacial atrophy and chronic hepatitis B virus infection

Abstract: Introduction:Progressive hemifacial atrophy (PHA) is a rare disorder characterized by unilateral facial atrophy affecting the skin, subcutaneous tissue, and fat, muscle, and osteocartilagenous structures creating a sunken hemiface appearance.Etiopathogenesis of PHA is poorly understood; no definitive treatment is currently available.Clinical Findings:We report a 41-year-old woman with PHA who showed an uncharacteristic “relapsing–remitting” evolution of brain lesions and was seropositive for hepatitis B virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Progressive hemifacial atrophy can be provoked by viral infections ( 43 ). Zhang and colleagues reported a 41-year-old woman with PHA who showed an uncharacteristic “relapsing-remitting” evolution of brain lesions and chronic HBV infection may have triggered the relapse in this case ( 113 ).…”
Section: Resultsmentioning
confidence: 86%
“…Progressive hemifacial atrophy can be provoked by viral infections ( 43 ). Zhang and colleagues reported a 41-year-old woman with PHA who showed an uncharacteristic “relapsing-remitting” evolution of brain lesions and chronic HBV infection may have triggered the relapse in this case ( 113 ).…”
Section: Resultsmentioning
confidence: 86%
“…Some patients with PRS exhibit a "relapsing-remitting" course, which is a common feature of MS (18). Our patient suffered from recurrent paroxysmal weakness of the right hand, but the symptom occurred for about 1 h almost every day for 3 years.…”
Section: Discussionmentioning
confidence: 72%
“…In addition to reports implicating autoimmunity, there are indications that PRS can be evoked by infection. Zhang et al (18) described a case of PRS that was apparently triggered by peripheral hepatitis B virus. Asanad (17) described a patient who developed PRS after herpes zoster infection, with post-herpetic neuralgia in the distribution of the ophthalmic division of the trigeminal nerve.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the patient's PRS followed a herpetic infection in the ophthalmic division of the trigeminal nerve with subsequent facial atrophy in the corresponding region. MRI revealed cerebral and periventricular white matter lesions, a hallmark pattern of MS. Intriguingly, the current patient presented with heat-induced horizontal diplopia on right lateral gaze with radiographic evidence of INO involving the MLF, a clinical presentation also consistent with MS. A recent report by Zhang et al showed that PRS may have a disease course similar to the “relapsing-remitting” subtype of MS as triggered by a chronic hepatitis B virus infection [14]. Infiltration of the central nervous system by immune cells and microbial infections likely serve as immunological triggers for demyelination in MS [15].…”
Section: Discussionmentioning
confidence: 99%
“…As the most common ocular manifestation of PRS, enophthalmos develops from retro-orbital fat or bone atrophy [14]. Patients with PRS may present with diplopia secondary to restricted ocular motility resulting from either ocular motor nerve dysfunction, extraocular muscle degeneration, or fibrosis [15].…”
Section: Introductionmentioning
confidence: 99%